A novel biosensor based on Blu-ray disc coating film for determination of total amino acid content in tea leaves. Issue 63 (13th December 2021) - Chu, Lanling; Wang, Yunzheng; Zhou, Yu; Kang, Xuejun
Abstract : The novel biosensor substrate material based on a simple BD coating film displayed preferable merits with high surface activity, low cost, easy making, easy using, and extensive application prospect. Abstract : Biosensor substrate materials are a key research focus in the field of sensors. Blu-ray discs (BDs) as universal sensor substrates are advantageous in comparison with other substrates (conventional paper and polycarbonate) in terms of easier activity treatment and higher density of reactive groups on the film surface. In this study, a novel and simple microfluidic biosensor based on BD coating film was developed by treating with sodium hydroxide solution and a piece of filter paper at slightly elevated temperatures. There are no significant physical damages to the substrate morphology, and the aging effect is minimal. The unique wetting, optical, and self-cleaning properties of the modified surfaces can be demonstrated in the paper. We have tested this new type of biosensor substrates for assay applications (the determination of total amino acids in tea leaves), which showed excellent performance in terms of sensitivity and reproducibility. The novel biosensor substrate material based on a simple BD coating film displayed preferable merits with easy making, low cost, easy using, and extensive application prospect.